White blood cells count as a risk factor of mortality in hemodialysis patients - راما علوش; تغريد قدار; ابراهيم سليمان (Latakia University Journal -Medical Sciences Series, 2022)
Background. Background. White blood cells play an important role in increasing blood viscosity and causing a change in idhesion properties in ischemia and cardiovascular disease, thus, the death rate invreases. The research aims to find a relationship between high number of white blood cells and the mortality in hemodialysis patients. Methods. The study included 139 hemodialysis patients (77 males and 62 females) at Al-Assad University Hospital and Tishreen University during the year 2018.The age distributions were similar between women and men.The percentage of smokers among men was higher than it was among women.Laboratory variables(complete blood count CBC,urea,creatinine,sodium,potassium,albumin,phosphorus)were obtained.The Chi-sqare-test was used to assess the difference in distribution of categorical variables for the study groups. The differences at significance level of P<0.05 were considered statistically significant. Results. The study showed that there are differences in the mean values of hematological parameters between the group of living patients and the group of deceased in this study within a year.The mean number of white blood cells, neutrophils, lymphocytes, platelets and urea were higher in the group of deceased than in the group of living patients. The erythrocyte count, hemoglobin, Mean Cell Volum (MCV), Mean Cell Hemoglobin (MCH), Sodium, potassium and creatinine were higher in the living patients than in the deceased group.The difference was statistically significant for the neutrophil to lymphocyte rate NLR, platelet count , mean platelet volume MPV and creatinine . (p<0.05).